Duals and Matrix Classes Involving Cesàro Type Classes of Sequences of Fuzzy Numbers - Hemen Dutta; Jyotishmaan Gogoi (Advances in Fuzzy Systems)
We first define Cesàro type classes of sequences of fuzzy numbers and equip the set with a complete metric. Then we compute the Köthe-Toeplitz dual and characterize some related matrix classes involving such classes of sequences of fuzzy numbers.